Ação antibacteriana da cetramida associada às solucões irrigadoras sobre Enterococcus Faecalis - Nascimento, Camila Almeida [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The aim of this study was to evaluate the action of conventional endodontic solutions such as sodium hypochlorite and chlorhexidine associated with cetrimide and QMiX, a commercial product composed by chlorhexidine, EDTA and cetrimide, on biofilm and planktonic phase of Enterococcus faecalis (ATCC 29212). The evaluated solutions were: G1: 2.5% Sodium Hypochlorite (NaOCl); G2: 2.5% NaOCl + 0.2% cetrimide (CTR); G3: 2% Chlorhexidine (CLX) 2%; G4: 2% CLX + 0.2% CTR; G5: 0.2% CTR; G6: QMiX. Saline solution was used as negative control. The study was divided into two chapters. In Chapter 1, the antibacterial activity of the solutions on microorganisms in planktonic phase and biofilm was evaluated. For direct contact with E. faecalis in planktonic phase, 50 μL of bacterial suspension were placed in tubes containing 1.45 mL of each irrigation solution or associations and after 1 and 3 minutes, neutralizing solutions were used to stop of the antimicrobial action of endodontic solutions. Decimal serial dilutions were performed and the suspensions were plated in Tryptic Soy agar medium (TSa). Dentin bovine blocks were used as substrate for induction of biofilms for 14 days. The biofilms were placed in contact with the solutions evaluated and transferred to test tubes containing neutralizing solution. After agitation for 60 seconds to suspend the remaining cells, decimal serial dilutions were performed and the suspensions were cultivated in triplicate on TSA plates. The incubation was held in microaerophilic at 37 ° C for 24 hours and the analysis was performed by counting CFU mL-1. The results were submitted to ANOVA and Tukey test, with significance level of 5%. All irrigating solutions and associations evaluated completely eradicated the microorganisms in planktonic phase. On biofilm, only NaOCl and NaOCl+CTR showed 100%- of bacterial elimination. CLX showed similar activity to CLX+CTR, CTR and QMiX after...

O objetivo do estudo foi avaliar a ação das soluções de hipoclorito de sódio e clorexidina associadas à cetramida e do QMiX, produto comercial que combina clorexidina, EDTA e cetramida, sobre Enterococcus faecalis (ATCC 29212) em fase planctônica e biofilme. As soluções avaliadas foram: G1: Hipoclorito de sódio (NaOCl) a 2,5%; G2: NaOCl a 2,5% + cetramida (CTR) a 0,2%; G3: Clorexidina (CLX) a 2%; G4: CLX a 2% + CTR a 0,2%; G5: CTR a 0,2%; G6: QMiX. Como controle negativo foi utilizada solução salina. O estudo foi dividido em dois capítulos. No capítulo 1, foi realizada a avaliação da atividade antibacteriana sobre os micro-organismos em fase planctônica e biofilme. Para o contato direto com E. faecalis em fase planctônica, 50 μl da suspensão bacteriana foram colocados em tubos contendo 1,45 mL de cada solução irrigadora ou associações e, após os períodos de 1 e 3 minutos foram utilizadas soluções neutralizantes da ação antimicrobiana dos irrigantes. Em seguida, foi realizada diluição decimal seriada e plaqueamento em meio Tryptic Soy agar (TSa). Para a indução dos biofilmes foram utilizados blocos de dentina bovina como substrato no período de 14 dias. Os biofilmes foram colocados em contato com as soluções avaliadas, e transferidos para tubos de ensaio contendo soluções neutralizantes. Após agitação por 60 segundos para a suspensão das células remanescentes, foi realizada diluição decimal seriada e plaqueamento em TSa em triplicata. A incubação foi realizada em microaerofilia a 37°C por 24 horas e a análise efetuada por meio da contagem de UFC mL-1. Os resultados foram submetidos aos testes ANOVA e Tukey, com nível de significância de 5%. Todas as soluções irrigadoras e associações avaliadas eliminaram completamente os micro-organismos em fase planctônica. Sobre biofilme, somente NaOCl e NaOCl+CTR apresentaram 100% de eliminação bacteriana...
Keywords: Endodontia; Enterococcus; Canal radicular - Irrigantes; Endodontics